Identifikasi Infrastruktur yang Berperan sebagai Peningkatan Pemberdayaan Masyarakat di Kampung Tridi Kota Malang - Damayanti, Fifi ; Ningrum, Diana (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2018)
Empowerment is a process of change that puts creativity and community initiatives to improve the quality of human life. One of them is the availability of infrastructure. This study aims to identify the infrastructure that plays a role in community empowerment to support the running of the Tridi tourist village. This village is located in RW 12, Kesatrian Village, Blimbing District, Malang. This study used descriptive qualitative method. The techniques used in research are observation, interview, and documentation techniques. Infrastructure in Tridi village, includes houses and buildings, road access, electricity systems and water supply, water and solid waste management systems. Infrastructure in the form of road access not only used as access for residents and visitors, but also used as parking lots and tourist spots. The houses?s wall and roads are used as a medium of 3D painting and become a spot for visitor to take photos. Along with the increasing number of visitors, efforts to increase community empowerment were also carried out, through counseling by making souvenirs from flannel fabrics and remaining of pine wood as entrance tickets for Tridi Village. This activity hold by PKK RW. The village development make the independence of the people who live in it increased. This is seen in the improvement of the economy, creativity, and social community. The increase in income is then reused to increase the quality of infrastructure so that it can become a empowered society.